Banco de dados e cadastro de consumidores: artigos 43/45 - Malheiros, José Eduardo (2008)
The dissertation herein is aimed at the obtaining of a Master´s degree provided by PUC-SP, in the specific area of Comsumer Relation Rights, as a part of Collective and Diffuse Rigths, and approaches the theme Data Banks and Consumer Registers Art. 43 to 45 of the C.D.C. (Brazilian Code of Consumers´ Defense). In its first part, (Items 1 to 4), this dissertation considers general aspects of Data Banks and Consumer Registers by means of their definitions, concepts and the history of their appearance at national and international level. In its second part (Items 5 to 8), the focus is on the information contained in the Data Banks and Consumer Registers in relation to the characteristics, period of effectiveness and time limit of such information, way of communicating it to consumers and information that is sub judice . In the final part (Items 9 to 14), the subject matter falls on more objective elements relating to the judicial procedure. Starting from the juridical nature of the Data Banks and Consumer Registers, which are considered entities of public character, it approaches the abusiveness committed by such entities; constitutional tutelage that is appropriate to the matter; responsibility for damages caused for consumers and the respective tutelage type that is applicable in accordance with their juridical nature. The end part draws a conclusion that Data Banks and Consumer Registers have their validity, but this fact cannot interfer in consumers´ rights and still less allow that suppliers reach their material objectives in a distorted way, with deflection from purpose, mainly by means of coercion and threats